Improved Algorithm of Radar Pulse Repetition Interval Deinterleaving Based on Pulse Correlation - Ge, Zhipeng; Sun, Xian; Ren, Wenjuan; Chen, Wenbin; Xu, Guangluan (IEEE access, 2019)
In the electromagnetic space, a single channel radar receiver will often intercept several periodic pulse trains radiating from the surrounding emitters simultaneously. The aim of radar pulse deinterleaving is to sort out the pulses coming from different emitters. Most traditional pulse repetition interval (PRI) deinterleaving methods are easy to sort out the pulses with small PRI fluctuations but difficult in dealing with relatively bigger fluctuation or staggered PRIs. In addition, this searching procedure can easily cause pulse omission phenomenon and even generate false pulses. In this paper, we propose an improved histogram method for PRI deinterleaving based on pulse correlation to overcome the above-mentioned shortcomings. After calculating the multi-level time difference histogram, we introduce the mean filter and interquartile range algorithm to optimize the estimated PRI values. Our method extracts the pulse pairs based on pulse correlation directly instead of searching for the pulses and then determines whether the PRI is staggered or not. The experiments on simulation data show that our method can achieve better performance on both the pulse trains of jittered PRIs and the staggered PRIs.